“Efecto de la aplicación de tres dosis de guano de isla en la productividad del maíz hibrido pioneer 30f87 en la estación experimental el porvenir-inia distrito de Juan Guerra Región de San Martín” - Ramirez Beteta, Luis Segundo (2014)
The present research was conducted in the field of Agricultura! Experimental Station "El Porvenir", in the valley of Bajo Mayo, Province of San Martin, geographically characterized by having the following coordinates: Longitude West 76 5 ', 6 35 'south latitude and 356 meters above sea level; in arder to evaluate the effect of dose (500- 1000-1500 kg.ha-1 ) of guano island in productivity simply modified maize hybrid Pioneer 30F87, determine the most appropriate dose of guano island in increasing productivity corn and perform economic analysis of the best dosages guano island. Performance and additional vegetative characteristics were evaluated using the statistical Randomized complete block design (DBCR) with 4 replications and 4 treatments, the results were analyzed by analysis of variance and multiple testing significance of Duncan. The experimental soil was residual origin and flat surface with clay loam, alkaline reaction (pH = 7.6), average orgariic matter content (2.3%) and medium nitrogen potassium and phosphorus content low. The planting distance was 0.80 m between rows and 0.35 m between strokes with a plant density of 71,428 plants per hectare. Composting was carried out using doses of 500, 1000 and 1500 kg of manure per hectare island the application was made at 1 O days after sowing when plants had three leaves and a total rainfall received during the growing period of 467.4 mm. From the results obtained according to the statistical analysis, it is concluded that there are significant differences between treatments in grain yield 14% of commercial moisture, whose yields fluctuated between 6.11 - 2.61 t.ha-1 corresponding to adose of 1 500 kg of manure per hectare island and treatment without guano island. According to agronomic characteristics evaluated and economic analysis (cost / benefit ratio), it was determined that the doses of 1 500 and 1 000 kg of island guano per acre, are best suited for increasing productivity by more than 40% and economically profitable, with net values exceeding 1,000 nuevos soles per hectare of production, with a 48% higher return and the importance of Guano island as a natural organic fertilizer and complete immediate uptake by plants, as organic and biodegradable product that improves the soil, increases productivity and improves the standard of living of the farmer Keywords: Productivity, planting distance, profitability, guano island.